Optimization Design and Simulation of Planar Eight-link Mechanism based on ADAMS - Chen Xinde (Jixie chuandong)
The mathematical model of the planar eight- bar mechanism is established by applying the theory of optimization design,on the basis of this,the ADAMS / View is used to establish the parametric model for the eight- bar mechanism as well as to conduct the optimization and movement simulation. The result of the optimization design and the simulation curves show that the method of optimization is feasible and fits exactly,so it can be provided for reference for the optimization design of the similar mechanism.